USING SCAMPER TECHNOLOGY FOR DEVELOPING STRATEGIC COMPETENCE OF B2 LEVEL STUDENTS (Ustozlar uchun, 2024)
This article mainly outlines SCAMPER technology, identifies its strengths and weaknesses and also promotes the ways of implementing this technology in the process of conducting foreign language lessons for the B2 level students who study in non-philological direction. The need for effective communication and cooperation between cultures and languages is more important than ever. Knowledge of foreign languages, especially English, has become an important asset for those who want to advance their education. As a result, the development of strategic competence in language learners at the B2 level has emerged as an important direction of language education. This article also explores the implementation of a system of tasks aimed at increasing the strategic competence of B2 students, providing them with the skills and confidence needed to navigate complex linguistic situations and excel in their chosen fields. In addition, this paper identifies the procedural part of the method as well as makes conclusions whether the accomplishment should be performed or not.